Identification and characterization of a novel 6′-N-aminoglycoside acetyltransferase AAC(6′)-Va from a clinical isolate of Aeromonas hydrophila - Zhang, Guozhi; Zhang, Lei; Sha, Yuning; Chen, Qiaoying; Lin, Naru; Zhao, Jingxuan; Zhang, Yuan; Ji, Yongan; Jiang, Weiyan; Zhang, Xueya; Li, Qiaoling; Lu, Junwan; et al. (Frontiers in Microbiology, 2023)
Background: Aeromonas species have been identified as agents responsible for various diseases in both humans and animals. Multidrug-resistant Aeromonas strains pose a significant public health threat due to their emergence and spread in clinical settings and the environment. The aim of this study was to determine a novel resistance mechanism against aminoglycoside antimicrobials in a clinical isolate.The function of aac(6')-Va was verified by gene cloning and antibiotic susceptibility tests. To explore the in vivo activity of the enzyme, recombinant proteins were expressed, and enzyme kinetics were tested. To determine the molecular background and mechanism of aac(6')-Va, whole-genome sequencing and bioinformatic analysis were performed.The novel aminoglycoside N-acetyltransferase gene aac(6')-Va confers resistance to several aminoglycosides. Among the antimicrobials tested, ribostamycin showed the highest increase (128-fold) in the minimum inhibitory concentration (MIC) compared with the control strains. According to the MIC results of the cloned aac(6')-Va, AAC(6')-Va also showed the highest catalytic efficiency for ribostamycin [kcat/Km ratio = (3.35 ± 0.17) × 10 4 M −1 • s −1 ]. Sharing the highest amino acid identity of 54.68%with AAC(6')-Ic, the novel aminoglycoside N-acetyltransferase constituted a new branch of the AAC(6') family due to its different resistance profiles. The gene context of aac(6')-Va and its close relatives was conserved in the genomes of species of the genus Aeromonas.The novel resistance gene aac(6')-Va confers resistance to several aminoglycosides, especially ribostamycin. Our finding of a novel resistance gene in clinical A. hydrophila will help us develop more effective treatments for this pathogen's infections.